2021
DOI: 10.1111/ggi.14255
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient knee pain after hip fracture surgery affects gait speed in older adults: A retrospective chart‐referenced study

Abstract: Aim Post‐hip fracture knee pain (PHFKP) develops in 28–37.4% of patients with hip fracture and contributes to prolonged hospitalization. Although reduced balance and gait speed contribute to falls, the effects of PHFKP remain unclear. This study aimed to clarify whether PHFKP is a factor in balance and gait speed. Methods We retrospectively reviewed the medical records of patients after hip fracture. Development of PHFKP, basic information, and physical function were examined. Berg balance scale (BBS) and maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Developing PHFKP did not affect FIM score at discharge but significantly increased the length of hospital stay (+6.8 days). Although this result is supported by previous studies, [4][5][6] caution should be exercised in generalizing our results, which were based on univariate analysis only. Obesity has been reported to increase the risk of postoperative comorbidities and prolonged hospital stay, 29 and the results of this study showed that the PHFKP group had a higher BMI.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Developing PHFKP did not affect FIM score at discharge but significantly increased the length of hospital stay (+6.8 days). Although this result is supported by previous studies, [4][5][6] caution should be exercised in generalizing our results, which were based on univariate analysis only. Obesity has been reported to increase the risk of postoperative comorbidities and prolonged hospital stay, 29 and the results of this study showed that the PHFKP group had a higher BMI.…”
Section: Discussionsupporting
confidence: 84%
“…We investigated the development of PHFKP for 1 week from admission. This was done for two reasons: (1) 85%-90% of PHFKP development has been reported to occur immediately after admission, 5,6 and (2) to minimize the temporal discrepancy between the time point and the admission assessment. KE-ROM was measured by a physical therapist using a goniometer in the admission assessment.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, elderly patients with hip fracture usually have poor body tolerance and a high rate of perioperative complications, among which cerebrovascular accidents are one of the most serious ones and also the leading cause of postoperative death [ 19 ]. Studies have shown many risk factors affecting cerebrovascular accidents, and currently, the well-established ones include history of cerebrovascular accidents, history of hypertension, general anesthesia, anesthetic drug dosage, and intraoperative blood pressure [ 20 , 21 ], in which general anesthesia is closely related to factors such as anesthetic drug dosage and intraoperative blood pressure, and therefore, it may be one of the most critical elements affecting cerebrovascular accidents.…”
Section: Discussionmentioning
confidence: 99%